Understanding Poorly Understood Chronic Illness: Lived Experiences, Healthcare Journeys, and Recommendations for Change - Woodville, Natalie (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2025)
Chronic health conditions present a substantial and growing challenge for healthcare systems worldwide. While much work has focused on improving care for common chronic illnesses, a significant gap remains in addressing the unique needs of patients with poorly understood, "contested" or "unexplained" conditions and symptoms. Employing a multi-method, multi-phase design with Patient and Public Involvement (PPI) embedded throughout, the present research examined the experiences of individuals living with a range of such conditions in Ireland, with a particular focus on their personal journeys and experiences with healthcare. Four studies were conducted over the four phases of research. First, a systematic literature review of qualitative studies (N=143) concerning patient and clinician experiences of medically unexplained symptoms, Fibromyalgia (FM) and Myalgic Encephalomyelitis (ME)/ Chronic Fatigue Syndrome (CFS) highlighted a key challenge of sensemaking at the limits of biomedical knowledge, which contributes to disbelief, invalidation, and suboptimal clinical management. Overarchingly, the synthesis revealed a lack of person-centeredness in healthcare and pointed to the patient-clinician dynamic as a viable target for change. Second, a cross-sectional, mixed-method online survey was conducted to explore the knowledge, understanding and perspectives on ME/CFS and FM among a sample of adults in Ireland (N=319). Findings highlighted stigma and invalidation as core challenges faced by individuals with these conditions. Most notably, responses revealed a troubling lack of confidence in the healthcare system among adults in Ireland, with pessimistic views of diagnosis and management, alongside negative appraisals of clinician knowledge and awareness of both ME/CFS and FM. The third study, utilising the Life Grid interview method with a phenomenological focus, involved an in-depth exploration of the lived experiences and healthcare journeys of individuals (N=12) with various poorly understood conditions, including FM, Ehlers-Danlos Syndrome, Postural Tachycardia Syndrome, Functional Neurological Disorder, ME/CFS and Long-COVID among others. Results provided a multidimensional account of the transformative impact of chronic illness on individuals' lifeworlds and, combined with exploratory patient journey maps, illustrated how individuals in Ireland struggle to navigate a poorly coordinated, "broken" system that fails to provide adequate care. Participants' accounts of being disbelieved and silenced highlighted complex power dynamics that exist between service users and healthcare practitioners, with overall results suggesting that integrated, multi-disciplinary and patient-centered care is lacking. Finally, with a view of identifying healthcare needs and developing actionable recommendations for change, five focus groups (N=24) were conducted in study four, eliciting patient views on targets for improvement in healthcare. PPI contributors were involved in the collaborative analysis of data collected, further ensuring that research outcomes were aligned with the needs and priorities of this population. A need for holistic and personalised approaches to care and the development of multidisciplinary clinics, networks and specialised diagnostic facilities were emphasised, as was a need for patient partnership in research. Overall the findings from this research reveal major gaps in care in the Irish healthcare system with two overarching implications: First, the research provides compelling evidence for a need to adopt an integrated, patient-centered model of healthcare delivery; and second, it highlights the need for meaningful, sustained patient and public engagement in research and healthcare design.
APPROVED
Keywords: Patient and Public Involvement; Phenomenology; Co-Design; Fibromyalgia; Myalgic Encephalomyelitis/ Chronic Fatigue Syndrome; Ehlers Danlos Syndrome; Postural Tachycardia Syndrome; Chronic Pain; Medically Unexplained Symptoms; Long-COVID; Poorly Understood Illness; Medical Uncertainty; Lived Experience; Qualitative Research; Healthcare; Patient Journeys; Chronic Illness